PART TIME REGISTRATION SYSTEM FOR UMM ALQURA UNIVERSITY - Alhawiti Khaled, 1979-, author; Suhaimi Ibrahim, Assoc. Prof. Dr., supervisor; Fakulti Sains Komputer dan Sistem Maklumat (Kuala Lumpur : Universiti Teknologi Malaysia, 2010)
Thesis